Metal-carbonyl organometallic polymers, PFpP, as resists for high-resolution positive and negative electron beam lithography. Issue 99 (20th October 2015) - Zhang, J.; Cao, K.; Wang, X. S.; Cui, B.
Abstract : Metal-carbonyl organometallic polymers, PFpP, can function as high-resolution resists for electron beam lithography. Abstract : Metal-containing resists for electron beam lithography (EBL) are attracting attention owing to their high dry etching resistance and possibility for directly patterning metal-containing nanostructures. The newly developed organometallic metal carbonyl polymers, PFpP, can function as EBL resists with strong etching resistance. One significant feature of the PFpP resist is its high resolution. Line arrays with line-widths as narrow as 17 nm have been created. The resist can also be used in positive tone.